Macrophyte-induced thermal stratification in a shallow urban lake promotes conditions suitable for nitrogen-fixing cyanobacteria - Vilas, M.; Marti, Clelia; Oldham, C.; Hipsey, M. (Springer, 2018)
© 2017, Springer International Publishing AG. Densely vegetated shallow lakes often experience low water column nutrient levels and reduced phytoplankton growth, but in some cases a high phytoplankton biomass can co-exist with subme rged macrophytes. The conditions that favour phytoplankton blooms within areas colonized by submerged macrophytes remain largely unexplored. We investigated changes in water quality variables and phytoplankton community composition data in relation to macrophyte-induced thermal stratification in a shallow urban lake. The results indicate that submerged macrophytes may favour internal loadings of phosphorus and low DIN:TP ratios, in periods when macrophyte-induced thermal stratification of the water column is common. Blooms of nitrogen-fixing cyanobacteria occurred under the strongly stratified conditions triggered by the high macrophyte biomass and elevated canopy, even though nitrogen limitation was apparent during the whole growing season. These findings suggest that submerged macrophytes can promote blooms of nitrogen-fixing cyanobacteria once they are sufficiently tall and dense to induce stable water column conditions.